2007
DOI: 10.1111/j.1365-2699.2006.01681.x
|View full text |Cite
|
Sign up to set email alerts
|

Track analysis of the marine palaeofauna from the Turonian (Late Cretaceous)

Abstract: Aim  To analyse the worldwide distribution patterns of Turonian marine biotas using a panbiogeographical approach. Location  Turonian localities of southern and north‐eastern Brazil, Mexico, Canada, central Europe, England and Morocco. Method  Panbiogeographical track analysis. Results  Nine generalized tracks and six nodes were found. The generalized tracks comprise two vicariant track patterns (one northern and one mid‐southern) across the Atlantic. Main conclusions  The generalized tracks show clearly two s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…During this same time period, from the late Cenomanian through to the early Turonian or later, a connection between the Tethys and the South Atlantic Ocean also likely existed (e.g., Ettachfini and Andreu, 2004), called the TransSaharan Seaway by Gallo et al (2007). Ichthyofaunal similarities exist between Morocco and South America (Cavin and Dutheil, 1999;Gallo et al, 2007;Murray and Wilson, 2009). However, this Atlantic connection seems perhaps to have been of shorter duration or influenced by some other factors that prevented the same level of exchange of fish taxa than that between eastern and western Tethys; the Tethyan species are more closely related to one another (in the same genus or family) than to species from western African localities or deposits in South and North American of similar age (shared families or higher taxa).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…During this same time period, from the late Cenomanian through to the early Turonian or later, a connection between the Tethys and the South Atlantic Ocean also likely existed (e.g., Ettachfini and Andreu, 2004), called the TransSaharan Seaway by Gallo et al (2007). Ichthyofaunal similarities exist between Morocco and South America (Cavin and Dutheil, 1999;Gallo et al, 2007;Murray and Wilson, 2009). However, this Atlantic connection seems perhaps to have been of shorter duration or influenced by some other factors that prevented the same level of exchange of fish taxa than that between eastern and western Tethys; the Tethyan species are more closely related to one another (in the same genus or family) than to species from western African localities or deposits in South and North American of similar age (shared families or higher taxa).…”
Section: Discussionmentioning
confidence: 94%
“…The Moroccan Agoult locality was deposited during a time when a transgressive event occurred, which would have enabled the Tethyan fauna to extend throughout northern Africa, reaching areas now in Morocco, Algeria, Tunisia, Libya, and Egypt, as well as those further south in Mali and Niger (Murray, 2000;Lopez-Arbarello, 2004;Murray and Wilson, 2009). During this same time period, from the late Cenomanian through to the early Turonian or later, a connection between the Tethys and the South Atlantic Ocean also likely existed (e.g., Ettachfini and Andreu, 2004), called the TransSaharan Seaway by Gallo et al (2007). Ichthyofaunal similarities exist between Morocco and South America (Cavin and Dutheil, 1999;Gallo et al, 2007;Murray and Wilson, 2009).…”
Section: Discussionmentioning
confidence: 94%
“…Craw 1982, Croizat 1984, Page 1987, Morrone 2001) and some recent studies confi rm the validity of the method to be applied to living and extinct species (e.g. Morrone 2006, Gallo et al 2007, 2010, Alzate et al 2008, Cavalcanti and Gallo 2008, Arzamendia and Giraudo 2009, Corona et al 2009, Espinosa-Pérez et al 2009, Maya-Martínez et al 2011.…”
mentioning
confidence: 91%
“…Some studies have been developed using geographic distributions of fossil fish applying methods of historical biogeography (e.g., Gallo et al 2007, Miguel et al 2014. Gallo et al (2007) analyzed the distributional patterns of Turonian marine biotas, including several fish taxa (e.g., lamniforms, pycnodontiforms, ichthyodectiforms, crossognathiforms, salmoniforms and aulopiforms).…”
Section: Introductionmentioning
confidence: 99%
“…Gallo et al (2007) analyzed the distributional patterns of Turonian marine biotas, including several fish taxa (e.g., lamniforms, pycnodontiforms, ichthyodectiforms, crossognathiforms, salmoniforms and aulopiforms). The authors concluded that final break-up of Gondwana and Laurasia was determinant vicariant event for biogeography of Atlantic Ocean and shaped the distributions of the Turonian biota.…”
Section: Introductionmentioning
confidence: 99%